STATE OF DIFFERENT LINKS OF HORMONAL-METABOLIC CHANGES IN PATIENTS WITH METABOLIC SYNDROME AND OBESITY - Mylytsya, K.M.; Biriuk, I.G.; Lavryk, A.S.; Mylytsya, M.M.; Shepitko, K.V. (World of Medicine and Biology, 2021)
The article is devoted to the problem of surgical treatment of patients with metabolic syndrome and obesity. Research methods: general clinical, anthropometric, laboratory, morphological; mathematical and statistical. It has been established that in order to select the optimal surgical tactics and predict complications in the postoperative period, it is necessary to additionally determine the insulin level. It has been proven that metabolic syndrome and obesity negatively affect the state of carbohydrate metabolism, production of inflammatory cytokines and cortisol. Assessment of changes in the structure of comorbidities (hypertension, joint pain) had no significant differences and in all groups was positive. The analysis of complications in all groups showed the absence of significant problems during the postoperative period, and there are minor differences of no discussion interest.
Keywords: obesity; insulin resistance; metabolic disorders; metabolic syndrome; surgical treatment; diabetes mellitus